A coarse frequency offset estimation in an OFDM system using the concept of the coherence phase bandwidth. - Keukjoon Bang
We propose a new coarse frequency offset estimation algorithm in orthogonal frequency-division multiplexing systems, which performs robust operation in the presence of a symbol timing offset within an allowed range. The effect of a symbol timing offset on estimating a coarse frequency offset is analyzed, and the coherence phase bandwidth according to the allowed symbol timing offset is introduced. The proposed algorithm adapts the concept of the coherence phase bandwidth for the purpose of weakening the effect of the symbol timing offset
Keywords: OFDM system; Coarse frequency offset estimation; Coherence phase bandwidth; Orthogonal frequency-division multiplexing systems; Symbol timing offset